Effect of weight training and flexible resistors in the development of some biomechanical variables of the last step and the throwing step and the completion of javelin throwing for young people - Abdulkareem, Rajaa; Abdulkareem, Jamal; Kamees, Omar Hameed; Ahmed, omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The research problem came according to the leak in the performance of javelin throwing game in Iraq compared to the Arab, Asian and international levels. This weakness may be attributed to many reasons such as failure to diagnose errors through kinetic analysis and preparation of training programs according to the analysis. Research in previous studies note that the achievement has reached the level of 96 meters, while the levels of achievement at the local level is still in the range of 70 meters, therefore, concerned and interested should propose modern training methods away from traditional methods. The study aimed to identify the impact of weight training and elastic resistors on some biomechanical variables in accomplishing javelin throwing for young people. The researchers also used the experimental approach to match the nature of the problem by designing a single experimental group. The research sample was selected from the players of the Diyala Youth Club for the javelin throwing event and they were selected in a deliberate manner. In addition to the field research procedures include visualizing procedures and extraction of biomechanical variables (final launched speed of the spear, absolute trunk angle and it’s time, momentum change, final body momentum (moment of push), primary body momentum, body angle approaching or pushing, angle between legs at the moment of the last step, The speed of the last step, in addition to the force and pressure of the two rear legs (fulcrum or pushing) and the front legs (based). the training curriculum lasted for eight weeks by three training units (weekly). The researchers concluded that the exercises that used have been developed and affected the pain Biomechanical changes and achievement of the research sample, where the evolution of the speed of the last step and the variables under study for the research sample as a result of training with special weights and resistors.